Cerebral blood flow velocity monitoring in pyogenic meningitis. Issue 1 (January 1993) - Goh, D; Minns, R A
Abstract : Transcranial Doppler ultrasound monitoring of cerebral blood flow velocity (CBFV) was performed on 17 children (age range 8 days to 6 years) with pyogenic meningitis. Serial measurements of the peak systolic, end diastolic, mean flow velocity, and resistance index (equal to peak systolic velocity minus end diastolic velocity divided by peak systolic velocity) were obtained over the period of their hospital admission. In all 16 survivors there was a significant decrease in the final resistance index compared with the initial resistance index due to a significant increase in the end diastolic velocity. There was a significant increase in the final mean flow velocity. In four patients the decrease in intracranial pressure and increase in cerebral perfusion pressure after mannitol infusions was accompanied by a corresponding decrease in resistance index and increase in mean flow velocity. A pressure passive CBFV response with a significant linear correlation for resistance index/mean arterial pressure may suggest a loss of cerebrovascular autoregulation. These results suggest that in the early phase increased cerebrovascular resistance may contribute to a relative impairment of cerebral perfusion. Non-invasive monitoring by transcranial Doppler ultrasound may be helpful for early detection of deterioration in cerebral haemodynamic trends.